The Sarcoplasmic/Endoplasmic reticulum Ca2+-ATPase (SERCA) is present in pig sperm and modulates their physiology over liquid preservation - Ferran Garriga; Jesús Martínez-Hernández; Ainhoa Parra-Balaguer; Marc Llavanera; Marc Yeste (Scientific Reports)
Abstract Liquid storage is the primary preservation method in the swine breeding industry because of its advantages over cryopreservation. Calcium (Ca2+), a key regulator of cell physiology, plays a crucial role during liquid preservation. Sarcoplasmic/Endoplasmic Reticulum Ca2+ ATPases (SERCA) belong to a family of P-type ATPases that regulate Ca2+ homeostasis within cells and have been previously described to play a function in the sperm of various mammalian species. Herein, we hypothesized that SERCA2 is present in pig sperm and is involved in the resilience of this cell to liquid preservation at 17 °C. For this purpose, sperm were incubated with different concentrations of thapsigargin (Thg; 0, 5, 25, and 50 µM) and stored at 17 °C for ten days. The presence and localization of SERCA2 were evaluated using immunoblotting and immunofluorescence, respectively. On days 0, 4, and 10, sperm motility was assessed using a computer-assisted sperm analysis (CASA) system, and sperm viability, membrane lipid disorder, acrosome integrity, mitochondrial membrane potential (MMP), and intracellular levels of Ca2+, superoxides and total reactive oxygen species (ROS) were evaluated by flow cytometry. We localized SERCA2 in the acrosome and midpiece of pig sperm. Furthermore, inhibition of SERCA with Thg resulted in reduced sperm viability and membrane stability, and increased MMP, and Ca2+ and ROS levels. In conclusion, the activity of SERCA prevents the accumulation of intracellular Ca2+ in sperm, which is detrimental to sperm quality and function during liquid storage at 17 °C. We thus suggest that the function of SERCA is crucial for the preservation of pig semen.